Competing protein-protein interactions regulate binding of Hsp27 to its client protein tau. Issue 1 (December 2018) - Freilich, Rebecca; Betegon, Miguel; Tse, Eric; Mok, Sue-Ann; Julien, Olivier; Agard, David; Southworth, Daniel; Takeuchi, Koh; Gestwicki, Jason
Abstract Small heat shock proteins (sHSPs) are a class of oligomeric molecular chaperones that limit protein aggregation. However, it is often not clear where sHSPs bind on their client proteins or how these protein-protein interactions (PPIs) are regulated. Here, we map the PPIs between human Hsp27 and the microtubule-associated protein tau (MAPT/tau). We find that Hsp27 selectively recognizes two aggregation-prone regions of tau, using the conserved β4-β8 cleft of its alpha-crystallin domain. The β4-β8 region is also the site of Hsp27–Hsp27 interactions, suggesting that competitive PPIs may be an important regulatory paradigm. Indeed, we find that each of the individual PPIs are relatively weak and that competition for shared sites seems to control both client binding and Hsp27 oligomerization. These findings highlight the importance of multiple, competitive PPIs in the function of Hsp27 and suggest that the β4-β8 groove acts as a tunable sensor for clients. Small heat shock proteins (sHSPs) limit the aggregation of proteins, such as tau. Here the authors show that Hsp27 recognizes two aggregation-prone regions of tau and that this interaction competes with Hsp27 oligomerization.